2022
DOI: 10.1016/j.echo.2022.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Transesophageal Echocardiogram in Patients with Cirrhosis and Esophageal Varices

Abstract: We read with interest the review article and meta-analysis by Hui and Leung 1 regarding the bleeding risk of transesophageal echocardiogram (TEE) performed in patients with esophageal varices. We concur with the authors' conclusion that TEE is associated with a low incidence of gastrointestinal bleeding in patients with gastroesophageal varices. In our retrospective, multicenter study of patients with cirrhosis who underwent TEE in the Mass General Brigham Health system, we identified no instance of overt gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The finding is supported by the recent systematic review and meta‐analysis that showed that the incidence of post‐TEE bleeding in patient with varices was low (0.84%, 95% confidence interval [CI] 0.34%–1.56%) and the bleeding risk was comparable between patients with and those without varices (risk difference, 0.26%; 95% CI, −0.80% to 1.32%; I 2 = 0%; p = 0.88) 11 . Based on the current findings, the presence or suspicion of esophageal varices should not delay urgent TEE and does not warrant upper endoscopy before procedure 12 …”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The finding is supported by the recent systematic review and meta‐analysis that showed that the incidence of post‐TEE bleeding in patient with varices was low (0.84%, 95% confidence interval [CI] 0.34%–1.56%) and the bleeding risk was comparable between patients with and those without varices (risk difference, 0.26%; 95% CI, −0.80% to 1.32%; I 2 = 0%; p = 0.88) 11 . Based on the current findings, the presence or suspicion of esophageal varices should not delay urgent TEE and does not warrant upper endoscopy before procedure 12 …”
Section: Discussionmentioning
confidence: 54%
“…11 Based on the current findings, the presence or suspicion of esophageal varices should not delay urgent TEE and does not warrant upper endoscopy before procedure. 12 To date, there is no specific treatment recommendation regarding the preferred antibiotic or duration for IE treatment in cirrhosis, particularly in LT candidates. A systematic review reported that aminoglycosides, vancomycin, and cephalosporins were the antimicrobials most frequently used for treatment of IE in cirrhosis.…”
Section: Discussionmentioning
confidence: 99%